Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/su151511945
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance Factors for the Social Norms Promoted by the Community-Led Total Sanitation (CLTS) Approach in the Rural Areas: Case Study of the Central-Western Region of Burkina Faso

Hemez Ange Aurélien Kouassi,
Harinaivo Anderson Andrianisa,
Maïmouna Bologo Traoré
et al.

Abstract: Although access to sanitation has been recognized as a fundamental human right, 3.6 billion people do not enjoy this right globally. In this group, the practice of unhealthy sanitation behaviors, such as open defecation (OD), is very common. To alleviate this problem, several governments in low-income countries have adopted Community-led Total Sanitation (CLTS). This is a participatory approach focused on ending OD and promoting good hygiene behaviors in target communities. This approach is centered around and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…But technological aspects alone are not sufficient to ensure the sustainability of a latrine. Social aspects are considered essential and, if not adequately addressed, the failure of the implemented solution is likely to occur [78][79][80]. A number of community, household, and structural factors besides technological factors were found to be associated with better toilet durability, including households with higher socioeconomic status, households with disabled members, living in communities with higher basic sanitation coverage, and having toilets in an area with a shallower water table [62,70].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…But technological aspects alone are not sufficient to ensure the sustainability of a latrine. Social aspects are considered essential and, if not adequately addressed, the failure of the implemented solution is likely to occur [78][79][80]. A number of community, household, and structural factors besides technological factors were found to be associated with better toilet durability, including households with higher socioeconomic status, households with disabled members, living in communities with higher basic sanitation coverage, and having toilets in an area with a shallower water table [62,70].…”
Section: Plos Onementioning
confidence: 99%
“…There are studies that have identified how participation in the selection process [86] optimizes people's ownership of the sanitation technique. Another important factor in determining the sustainability of a given technology is its social acceptance by the local community [68,78,87]. It is important to analyze user feedback on how technologies are planned and implemented [88].…”
Section: Plos Onementioning
confidence: 99%